2021
DOI: 10.1097/md.0000000000026829
|View full text |Cite
|
Sign up to set email alerts
|

Intertrochanteric valgus osteotomy for post-traumatic coxa vara after proximal femur fractures

Abstract: To investigate the clinical effects of a new intertrochanteric valgus osteotomy technique designed by the authors for treatment of post-traumatic coxa varus after proximal femur fractures. Retrospectively analyzed 11 patients who developed coxa vara after sustaining proximal femoral fractures were treated with intertrochanteric valgus osteotomy from December 2005 to December 2018 in our hospital. This study included 6 cases of intertrochanteric fracture deformity union, 3 cases of subtrochanteric fracture nonu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 19 publications
(43 reference statements)
0
1
0
1
Order By: Relevance
“…Limping and limb length discrepancy accounted for a less score. Tian S et al 18 have showed improvement in Harris Hip score upto 93.1 and Magu et al 6 showed average of 86.7. In THR, the average Harris hip score was 84.135± 8.87 which was not statistically significant indicating that irrespective of the nature of surgery, there is definitive improvement of hip function post operatively.…”
Section: Discussionmentioning
confidence: 99%
“…Limping and limb length discrepancy accounted for a less score. Tian S et al 18 have showed improvement in Harris Hip score upto 93.1 and Magu et al 6 showed average of 86.7. In THR, the average Harris hip score was 84.135± 8.87 which was not statistically significant indicating that irrespective of the nature of surgery, there is definitive improvement of hip function post operatively.…”
Section: Discussionmentioning
confidence: 99%
“…(Palmer et al, 2021). Na coxa vara é frequente as queixas de dores crônicas no quadril, desproporção do comprimento dos membros inferiores, fraqueza do glúteo, claudicação e limitação do movimento de abdução do quadril, sintomas e sinais que afetam significativamente a qualidade de vida dos portadores dessa condição (Tian et al, 2021).…”
Section: Autor Títulounclassified